2015
DOI: 10.2106/jbjs.n.01272
|View full text |Cite
|
Sign up to set email alerts
|

An Alumina Ceramic Total Talar Prosthesis for Osteonecrosis of the Talus

Abstract: Background: Treatment of osteonecrosis of the talus is challenging. Total talar replacement has the potential to restore the function of the ankle joint without an associated leg-length discrepancy. The purpose of the present study was to investigate postoperative function and pain after total talar replacement in patients with osteonecrosis of the talus.Methods: Fifty-five ankles in fifty-one consecutive patients with osteonecrosis of the talus who were treated with a total talar replacement from 2005 to 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(139 citation statements)
references
References 25 publications
(25 reference statements)
2
135
0
2
Order By: Relevance
“…Total talar replacement with a prosthesis, first performed by Taniguchi et al in 2005, is considered to be an optimal treatment for extensive aseptic necrosis of the talus, and traumatic loss of talus. 10 Preservation of the joint motion and shorter recovery are the major advantages over traditional surgical options. And we believe it would also be of significance in treating talus tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Total talar replacement with a prosthesis, first performed by Taniguchi et al in 2005, is considered to be an optimal treatment for extensive aseptic necrosis of the talus, and traumatic loss of talus. 10 Preservation of the joint motion and shorter recovery are the major advantages over traditional surgical options. And we believe it would also be of significance in treating talus tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Both were found to have an acceptable clinical outcome but also caused a few problems. Taniguchi et al voiced concern about loosening and sinking between the talar body prosthesis and the talar neck [6] and recommended using a third-generation prosthesis that completely replaces the talus [7]. As in our two cases, Ando et al found that total replacement with a third-generation talar prosthesis for necrosis of the talus achieved a much better outcome in a 72-year-old woman at 2 years after surgery [23].…”
Section: Discussionmentioning
confidence: 85%
“…Taniguchi et al [7] and Ando et al [23] have reported that total talar replacement with an alumina ceramic prosthesis is the most suitable treatment for necrosis of the talar body. In their cases, patients proceeded to early rehabilitation after surgery with improved range of motion at the ankle and pain-free walking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ligaments attach the talus to its surrounding articular structures [12]. Based on these exclusive characteristics, the talus is prone to several pathologies and injuries, but the native talus is difficult to reconstruct or duplicate in patients with conditions such as peritalar instability [13], talar bone damage [14], and loss of the talus [2]. Several reports have proposed the characteristics of the talus in terms of its biomechanical and morphologic aspects.…”
Section: Plos Onementioning
confidence: 99%